Chewing lice of genus Myrsidea (Phthiraptera: Menoponidae) from Turdidae (Passeriformes) of Costa Rica, with descriptions of seven new species - Kounek, Filip; Sychra, Oldrich; Capek, Miroslav; Literak, Ivan (Zootaxa, 2013)
A total of 166 individuals from 10 bird species belonging to the family Turdidae were examined for chewing lice in Costa Ricaduring 2004, 2009 and 2010. A total of 12 species of the louse genus Myrsidea were collected from 54 birds, including four previously named, seven new undescribed species, and one identified as Myrsidea sp. Names, descriptions and illustrations are given for the seven new species of Myrsidea. They and their type hosts are: Myrsidea assimilis sp. nov. ex Turdus assimilis (Cabanis, 1850), M. cerrodelamuertensis sp. nov. ex Catharus gracilirostris (Salvin, 1865), M. hrabaki sp. nov. ex Myadestes melanops (Salvin, 1865), M. obsoleti sp. nov. ex Turdus obsoletus (Lawrence, 1862), M. quinchoi sp. nov. ex Catharus frantzii (Cabanis, 1861), M. tapanti sp. nov. ex Catharus fuscater (Lafresnaye, 1845), and M. tapetapersi sp. nov. ex Turdus nigrescens (Cabanis, 1861). Records of four named and one unidentified species of Myrsidea from other Costa Rican thrushes are also given and discussed.